Bilingualism in francophone literatures in Central and Eastern Europe: the experience of exile (Colloquia Comparativa Litterarum, 2025)
The article examines the experience of exile among writers who have emigrated from Central and Eastern Europe (Agota Kristof, Emile Cioran, Milan Kundera, Julia Kristeva, Tzvetan Todorov) by establishing the concepts of exile, uprooting and disorientation. The in-between-languages shows the memory of the mother tongue and the situation of permanent discomfort in the adopted language – French.
Keywords: exile; bilingualism; Central and Eastern Europe; in-between-languages; Francophone